Critical role of KRAS mutation in pancreatic ductal adenocarcinoma - Fan, Zhiyao; Fan, Kun; Yang, Chao; Huang, Qiuyi; Gong, Yitao; Cheng, He; Jin, Kaizhou; Liu, Chen; Ni, Quanxing; Yu, Xianjun; Luo, Guopei (Translational Cancer Research; Vol 7, No 6 (December 30, 2018): Translational Cancer Research, 2018)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal human cancers worldwide. Little progress has been made in recent years concerning its diagnosis and treatment. Genetic alterations can be found in approximately 97% of PDAC cases. Mutations in the KRAS gene, which encodes the KRAS protein that regulates cell proliferation, differentiation, and apoptosis via activation of downstream signal transduction pathways, occur most frequently. KRAS plays a pivotal role in modulating the tumor microenvironment in PDAC patients. Additionally, KRAS can regulate metabolic changes in PDAC cells in a variety of ways. Although previous studies have shown that KRAS mutation detection can be used for early diagnosis and to predict the prognosis of PDAC patients, and many paths have been proposed to suppress the effects of KRAS, there is still no single pathway that leads to effective treatment of KRAS-mutant PDAC. This review summarizes the role of KRAS mutation in PDAC and examines the association between KRAS mutation and clinical applications.